Innovative Solution in Interior Design Decoration (The Peerian Journal, 2022)
The use of modern high technologies is a prerequisite for the development of a professional design studio. We designers keep up with the times and follow the latest innovations in the field of interior design. This article presents modern types of decoration technology. Below are the innovative solutions we use to create interiors